Republic of Kosovo : Fifth Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses Kosovo's Fifth Review Under the Stand-by Arrangement. All end-August 2013 and continuous performance criteria were met, as a renewed shortfall in customs collection was over-compensated by underexecution of spending. A prior action on issuing a government decision that specifies the nonallocation of Euro 88 million across expenditure categories was also met. The applicable structural benchmarks were met on substance. Missed by small margins were the indicative targets on the nonaccumulation of domestic payments arrears by the central and general governments. The IMF staff supports the authorities' request for completion of the fifth review under the Stand-By Arrangement.